2020
DOI: 10.24036/jptk.v3i1.3723
|View full text |Cite
|
Sign up to set email alerts
|

Needs Analysis in Learning Media Development Based on Augmented Reality (AR) for Computer Network Installation Courses

Abstract: This needs analysis research consists of field studies and literature studies. Where the purpose of this research is; 1) description of student achievement values and learning processes, 2) the uses and constraints faced by students in the use of learning media Computer Network Installation, 3) formulation of instructional media needed in learning computer network installation. This research belongs to the type of qualitative descriptive research. The subjects of this study were 29 students of Informatics Engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…The level of validity obtained is 84.75 % with the category suitable for use in learning. Previous study found that the learning products made were also valid to use (Mubai et al, 2020). Meanwhile, at the practical level, it was obtained at 86.64% with a very practical category, which means that mobile learning by Edmodo is very practical to use in learning activities.…”
Section: Discussionmentioning
confidence: 84%
“…The level of validity obtained is 84.75 % with the category suitable for use in learning. Previous study found that the learning products made were also valid to use (Mubai et al, 2020). Meanwhile, at the practical level, it was obtained at 86.64% with a very practical category, which means that mobile learning by Edmodo is very practical to use in learning activities.…”
Section: Discussionmentioning
confidence: 84%
“…Data collection assesses the effectiveness of PjBL-STEAM in determining student learning outcomes across cognitive, affective, and psychomotor abilities [31]. Data analysis will utilize SPSS software, employing descriptive statistical analysis for pre-test and post-test values, standard deviation, and data significance levels to inform subsequent decisions [32], [33].…”
Section: Data Analysis Techniquementioning
confidence: 99%
“…Need analysis is an analysis conducted to examine a phenomenon of the needs of a program (Mubai et al, 2020). Respondents used in filling out this needs analysis questionnaire are teachers of Vocational High Schools majoring in mechanical engineering in Padang City.…”
Section: Needs Analysis and Development Of Constructivist Feedback-ba...mentioning
confidence: 99%